2009
DOI: 10.1182/blood-2008-04-152934
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 expression enhances vascular endothelial resistance to complement-mediated injury through induction of decay-accelerating factor: a role for increased bilirubin and ferritin

Abstract: Catabolism of free heme by heme oxygenase-1 (HO-1) generates carbon monoxide, biliverdin, and free iron (Fe). These end-products are responsible for much of the biologic activity of HO-1, including anti-inflammatory, antiapoptotic, antiproliferative, and antioxidant effects. We have identified an additional cytoprotective action, the regulation of complement activation, mediated via induction of decay-accelerating factor (DAF) . IntroductionVascular endothelial cells (ECs) express constitutive and inducible cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 51 publications
1
67
1
Order By: Relevance
“…20 In addition, our previous studies have observed that serum bilirubin has a tight correlation with baPWV. Furthermore, baPWV has been used as an index of subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, our previous studies have observed that serum bilirubin has a tight correlation with baPWV. Furthermore, baPWV has been used as an index of subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, heme oxygenase 1 and heme degradation products could attenuate complement-mediated acute inflammation and protect human vascular endothelial cells against complement-mediated injury. 20 In addition, our previous studies have observed that serum bilirubin has a tight correlation with baPWV. Furthermore, baPWV has been used as an index of subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Heme suppressed macrophage hROS ( Figure 4A), and this protection was strongly reversed in the presence of the specific HO-1 inhibitor 10 mol/L zinc protoporphyrin 19,20 ( Figure 4B). Zinc protoporphyrin also reduced macrophage survival in culture over 6 days, whereas both heme and the specific HO-1 activator cobalt protoporphyrin 19,20 had the opposite effect, each in a concentration-dependent manner over 100 nmol/L to 10 mol/L ( Figure 4C). Furthermore, both the increase in CD163 and suppression of HLA-DR induced by heme were antagonized by zinc protoporphyrin (300 nmol/L-3 mol/L) ( Figure 4D).…”
mentioning
confidence: 99%
“…Cultured human ECs upregulate CD55 and CD59 when stimulated with pathogenic antibodies, C5b-C9, thrombin and other pro-inflammatory molecules such as TNF [109,110]. Other studies suggest antiapoptotic proteins such as BCL-2 and haem oxygenase 1 (HO1) upregulate CD55 thereby enhancing endothelial resistance and promoting accommodation of the graft [111]. ECs also modulate T cell function and expansion through local production of complement and CD88 signalling on T cells seen in heart and kidney transplantation models [112,113].…”
Section: Complement and The Coagulation Systemmentioning
confidence: 99%